Feeling Happy and Sad at the Same Time? Subcultural Differences in Experiencing Mixed Emotions between Han Chinese and Mongolian Chinese - Deng, Xinmei; Ding, Xuechen; Cheng, Chen; Chou, Hiu Mei (Frontiers in Psychology, 2016)
Sometimes people experience pleasant and unpleasant emotions at the same time in a single emotional event. Previous cross-cultural studies indicated that such mixed emotions are more prevalent in China and related to the attitudes toward happiness and individual’s regulatory motivation. However, China is a multi-ethnic country and not much is known about subcultural differences in mixed emotions. The aim of this study was to examine the role that implicit attitudes toward happiness and regulatory motivation played in regard of the subcultural differences in mixed emotions between Han (N = 61) and Mongolian Chinese (N = 46). Results indicated that, compared with Mongolian Chinese, Han Chinese showed stronger associations between implicit contra-hedonic attitudes toward happiness and mixed emotions during pleasant emotional events. Also, Han Chinese who reported contra-hedonic motivation during pleasant emotional events had higher levels of mixed emotions than those who had hedonic motivation. No significant differences were found in terms of mixed emotions between Mongolian Chinese who had contra-hedonic and hedonic motivation. These results suggest that the psychological mechanisms underlying differences in mixed emotions also require a more comprehensive understanding from a subcultural perspective.